2008
DOI: 10.1152/ajpcell.00234.2008
|View full text |Cite
|
Sign up to set email alerts
|

Chemotoxicity of doxorubicin and surface expression of P-glycoprotein (MDR1) is regulated by the Pseudomonas aeruginosa toxin Cif

Abstract: Ye S, MacEachran DP, Hamilton JW, O'Toole GA, Stanton BA. Chemotoxicity of doxorubicin and surface expression of Pglycoprotein (MDR1) is regulated by the Pseudomonas aeruginosa toxin Cif.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…17 To date, Cif, a secreted toxin from Pseudomonas aeruginosa, is the only bacterial component identified to selectively reduce the apical plasma membrane expression of P-gp in a variety of epithelial cells, including airway, intestinal and renal epithelial cells. 20 These results are consistent with a role for P-gp in the maintenance of homeostasis in the gastrointestinal tract and support the emerging concept of a protective role for this transporter in shielding the host not only from harmful xenobiotics, but also from invading bacterial pathogens. Of note, attempts are currently being made to harness the ability to S. typhimurium and Cif to impair P-gp for the purposes of enhancing the utility of chemotherapeutics towards their target.…”
Section: Introductionsupporting
confidence: 85%
“…17 To date, Cif, a secreted toxin from Pseudomonas aeruginosa, is the only bacterial component identified to selectively reduce the apical plasma membrane expression of P-gp in a variety of epithelial cells, including airway, intestinal and renal epithelial cells. 20 These results are consistent with a role for P-gp in the maintenance of homeostasis in the gastrointestinal tract and support the emerging concept of a protective role for this transporter in shielding the host not only from harmful xenobiotics, but also from invading bacterial pathogens. Of note, attempts are currently being made to harness the ability to S. typhimurium and Cif to impair P-gp for the purposes of enhancing the utility of chemotherapeutics towards their target.…”
Section: Introductionsupporting
confidence: 85%
“…1). Cif has also been shown to reduce the epithelial cell expression of another ABC transporter, P-glycoprotein, a drug efflux pump highly expressed in cancer; however, other drug efflux ABC transporters like MPR1 and MPR2 are not affected by Cif (56). These studies have been performed with cultured epithelial cells, which may limit the possible range of Cif targets; thus, additional Cif virulence effects may be seen in an animal model.…”
Section: Cif a Novel Virulence Factormentioning
confidence: 99%
“…Helicobacter pylori infection was also shown to be associated with P-gp overexpression in the intestine (68), whereas Salmonella enterica serovar Typhimurium was shown to dampen P-gp function in order to promote epithelial cell invasion (69). In the case of Pseudomonas aeruginosa, it was shown that the bacteria secrete a toxin, called Cif, which selectively inhibits P-gp expression in a variety of epithelial cells (70). Taken together, these examples indicate an intimate interaction between bacterial pathogens and P-gp, though the molecular mechanisms that govern this interaction and their association with the innate immune system are not clear.…”
Section: Discussionmentioning
confidence: 99%